2022
DOI: 10.4254/wjh.v14.i7.1307
|View full text |Cite
|
Sign up to set email alerts
|

Small extracellular vesicles and liver diseases: From diagnosis to therapy

Abstract: Extracellular vesicles (EVs), especially small EVs (sEVs) derived from liver cells, have been the focus of much attention in the normal physiology and pathogenesis of various diseases affecting the liver. sEVs are approximately 100 nm in size, enclosed within lipid bilayers, and are very stable. The lipids, proteins, and nucleic acids, including miRNAs, contained within these vesicles are known to play important roles in intercellular communication. This mini-review summarizes the application of sEVs. First, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…In diseased states, they exacerbate injury by initiating numerous inflammatory signaling cascades. The latter is particularly true in nonalcoholic steatohepatitis (NASH) where an increase in the number of circulating EVs correlates to disease progression ( Kakazu et al, 2016 ; Tsuchiya et al, 2022 ). However, the mechanism by which inflammation alters the biogenesis and disease-associated changes in exosomal cargoes is not fully known.…”
Section: Discussionmentioning
confidence: 99%
“…In diseased states, they exacerbate injury by initiating numerous inflammatory signaling cascades. The latter is particularly true in nonalcoholic steatohepatitis (NASH) where an increase in the number of circulating EVs correlates to disease progression ( Kakazu et al, 2016 ; Tsuchiya et al, 2022 ). However, the mechanism by which inflammation alters the biogenesis and disease-associated changes in exosomal cargoes is not fully known.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on their functional role in HCC, it is reported that there is a great production of small extracellular vesicles (sEVs) (30–130 nm) from malignant hepatocytes, allowing cross-talk communication between HCC cells, in order to enhance cell proliferation, migration, and invasion, as well as metastatic dissemination [ 119 ]. There are several exosomal miRNAs that can be potentially isolated from serum, plasma, and urine, which can be utilized as diagnostic tools and prognostic or predictive biomarkers for HCC [ 120 , 121 , 122 , 123 , 124 ].…”
Section: The Interplay Between Evs and Mirnas In Hccmentioning
confidence: 99%